Comparative analysis of translation on harf Jar lam in surah Al - Baqarah By Abdullah Yusuf Ali and Muhammad Marmaduke Pickthall - Wafa'ul Afifah (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri, 2023)
et,1/Mumtaz c.1